Blood eosinophil count as a predictor of hospital length of stay in COPD exacerbations. Issue 3 (6th August 2019) - Ko, Fanny W.S.; Chan, Ka Pang; Ngai, Jenny; Ng, So‐Shan; Yip, Wing Ho; Ip, April; Chan, Tat‐On; Hui, David S.C.
ABSTRACT: Background and objective: Airway inflammation accompanying exacerbations varies among individuals with some having neutrophilic, while others showing eosinophilic inflammation. This study assessed the cut‐off values of blood eosinophil count for identifying subjects with longer hospital length of stay (LOS) with acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Methods: Patients were recruited at presentation to the hospital with an AECOPD. Complete blood picture with differential count was taken on admission. Patients were treated with a standard course of systemic corticosteroid and antibiotic and evaluated at 8 weeks post‐exacerbation for lung function measurement and 6‐min walk. They were followed up in 1 year for any readmissions or mortality. Cut‐off values of eosinophils for assessment of longer LOS were calculated using receiver operating characteristic (ROC) curve analysis. Results: A total of 346 patients with admission eosinophil count were included in the analysis (333 (96.2%) were males; mean ± SD age: 74.9 ± 7.8 years; mean forced expiratory volume in 1 s (FEV1 ): 43.4 ± 16.3% predicted). The median (interquartile range (IQR)) of the absolute peripheral eosinophil count, percent eosinophil count and LOS were 0.11 (0.25) × 10 9 /L, 1 (3) % and 5 (7) days, respectively. Using the median LOS of ≥5 days as the cut‐off, ROC analysis of the cut‐off value of eosinophil count associated with longer LOS was at <2% (area under the curve (AUC): 0.666, P < 0.001) while absolute eosinophil count was at <0.144 × 10 9 /L (AUC: 0.645, P < 0.001). These eosinophil cut‐off values could predict longer LOS independent of age, lung function and previous hospital admissions, but had no association with readmissions for AECOPD and mortality at 12 months. Conclusion: An eosinophil value of <0.144 × 10 9 /L on admission or <2% was associated with longer hospital LOS for AECOPD. Abstract : For patients hospitalized for acute exacerbations of chronic obstructive pulmonary disease (AECOPD), an eosinophil count at a cut‐off value of <2% of the total leucocyte count or an absolute count of <0.144 × 10 9 /L was associated with a longer length of stay (LOS) independent of other factors including age, gender, past history of exacerbations and lung function. See related Editorial